2018
DOI: 10.3390/ma11030433
|View full text |Cite
|
Sign up to set email alerts
|

Wear Behaviours and Oxidation Effects on Different UHMWPE Acetabular Cups Using a Hip Joint Simulator

Abstract: Given the long-term problem of polyethylene wear, medical interest in the new improved cross-linked polyethylene (XLPE), with or without the adding of vitamin E, has risen. The main aim of this study is to gain further insights into the mutual effects of radiation cross-linking and addition of vitamin E on the wear performance of ultra-high-molecular-weight polyethylene (UHMWPE). We tested four different batches of polyethylene (namely, a standard one, a vitamin E-stabilized, and two cross-linked) in a hip joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Preclinical endurance testing has become a standard procedure to predict the mechanical performance of new devices during their development. Wear tests are performed on different materials and designs used in prosthetic implants [ 1 , 6 , 7 , 8 ] to obtain quality assessment and acquire further knowledge about the tribological processes of joint prostheses. The objective of these investigations is to find out the wear rate and its dependence on the test conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical endurance testing has become a standard procedure to predict the mechanical performance of new devices during their development. Wear tests are performed on different materials and designs used in prosthetic implants [ 1 , 6 , 7 , 8 ] to obtain quality assessment and acquire further knowledge about the tribological processes of joint prostheses. The objective of these investigations is to find out the wear rate and its dependence on the test conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The present investigation was a continuation of a previous study ( 19 ), in which the wear behavior of the above-mentioned four sets of cups was examined together with their surface topography, cross-linking density, and oxidation state of pristine materials. Surface topography analyses revealed that worn STD and VE cups had smoother surfaces than XL-50 and XL-75 samples; VE cups showed the lowest roughness and delamination ( 19 ).…”
Section: Introductionmentioning
confidence: 88%
“…The present investigation was a continuation of a previous study ( 19 ), in which the wear behavior of the above-mentioned four sets of cups was examined together with their surface topography, cross-linking density, and oxidation state of pristine materials. Surface topography analyses revealed that worn STD and VE cups had smoother surfaces than XL-50 and XL-75 samples; VE cups showed the lowest roughness and delamination ( 19 ). In the present study, we decided to integrate the already obtained results with a molecular characterization of the materials through micro-Raman spectroscopy to link the Raman results to the surface topography data and to gain more insight into the wear mechanism.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Currently used ceramics, X-linked Polyethylene, and metal have various disadvantages and wear with time [2,[4][5][6]14]. Metal on Metal (MoM) was abandoned due to metal ion release and pseudo-tumor production [3].…”
Section: Introductionmentioning
confidence: 99%